O bebê com Síndrome de Down : um estudo no Centro de Educação Infantil Criarte-Ufes - Dias, Israel Rocha (2015)
This study titled - "the baby with Down syndrome: a study in Early Childhood Center Criarte-Ufes" presents survey data produced in a survey in the course of Master of Education in the Graduate Program of the Federal University of Espirito Santo -UFES. We aimed to: describe and understand the process of adding a baby with Down syndrome in the CIS Early Childhood Center - Criarte - Ufes. Specifically, it was intended to: (a) describe the main characteristics, peculiarities and characteristics of Down syndrome; (b) understand the context of early childhood education, the pedagogical practices developed with a focus on inclusion baby with Down syndrome; (c) describe and discuss ways of organizing a school of federal early childhood education for the care and inclusion baby with Down syndrome, from the historical and cultural contribution. In preparing this study, the adopted methodological approach, from the qualitative, took the picture of the case study with descriptive approach in a historical and cultural perspective, talking mainly with Vygotsky and his followers who understand the human being as a being who, regardless physical, mental or sensory characteristics, produces knowledge and culture while it appropriates the culture and knowledge of other subjects of their social group. The purpose of this research is not to raise a single die and yes, describe and understand how Luke's inclusion process, research subject, happens, from involvement in situ context. In short, it may be emphasized that such specific goals led to fully reach the general objective of this study as it allowed understand, describe and understand the inclusive daily life of this baby. In addition, the study found that when school children's education and their professionals understand the subject with or without disabilities is subject producer of history and culture, they tend to work in the sense that this guy can and should be part of all routine as an active member of the teaching-learning process